Portrayal of Gender Roles in Selected Nollywood Movies - Omotola Ogunbola; Gbemisola Adebayo; Omolara Akin-Odukoya; Subulola Etimiri (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2024)
This study examined the portrayal of gender roles in selected Nollywood movies. The study objectives were to; analyze the depiction of women in domestic/familial roles compared to men in Nollywood movies. The study employed both the cultivation theory and gender schema theory to serve as theoretical frameworks for this research. The research design employed in this study is the content analytical design which specifically involves systematic examination of communications to objectively describe and quantify phenomena and the population of the study were the Nollywood movies produced between 2012 and 2020. Iya Alalake (2012), Oloture (2018), Isoken (2017) and The Wedding Party (2016) were selected for the analysis because these movies characteristics represent cultural representation, critical acclaim and exploration of gender themes. The findings reveal that the study on gender portrayal in four Nigerian films can be compared and contrasted with previous studies that have analyzed Nigerian film and other cultural contexts. This confirms that the films are reiterating certain patriarchal expectations while advocating for renewal. In addition, previous content analyzes of African films have emphasized their use of narratives and multiple layers to effectively construct gendered narratives. This study reflects this and sees how films like Isoken and Aya Alalake show many inspiring women who defy the odds through education and participation without killing. The study recommends that there should be an increase the funding and distribution of films with outstanding women and relationships that are stronger than the characters. Also, provide literacy instruction to help audiences interpret social situations and think from new perspectives.